Metalinguistic Awareness on Academic Registers of EFL Higher Education Students - Mokodompit, Kessy Pramesti; Tanipu, Zulkifli; Bay, Indri Wirahmi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Metalinguistic awareness plays a crucial role in language acquisition, particularly in academic contexts where precise language use is essential. This study investigates the metalinguistic awareness of English as a Foreign Language (EFL) students, focusing on word-specific orthographic awareness. The research explores the current state of students' awareness and identifies factors influencing their ability to recognize and correct orthographic errors in academic writing. Employing a think-aloud protocol and interviews, the study examines students' cognitive processes while engaging in word-specific orthographic tasks. Findings indicate that students demonstrate varying levels of awareness, categorized into intuition, noticing, meta-awareness, and understanding of underlying rules. Key factors influencing their awareness include linguistic background, exposure to English, and academic experience.